Programming voice interfaces : giving connected devices a voice - Quesada, Walter; Lautenbach, Bob (O'Reilly Media, 2018)
Get a step-by-step guide for developing voice interfaces for applications and devices connected to the Internet of Things. By allowing consumers to use natural human interactions, you can avoid awkward methods of input and interactivity to provide them with elevated user experiences. This practical book is ideal for software engineers who build applications for the Web, smartphones, as well as embedded systems that dominate the IoT space. Integrate voice interfaces with internet connected devices and sensors Learn how to integrate with existing voice interfaces Understand when to use a voice over other Natural User Interface technologies Build a prototype with tools such as Raspberry Pi, solderless breadboards, jumper cables, sensors, Arduino, Visual Studio, and other tools Use cloud services such as Azure and AWS to integrate voice with your existing or new web service end-points.